Creating Animation as Audiovisual Media Learning to Improve Motivation and Social Subject Outcome of 5th grade of Elementary School at SD Negeri 067245 Medan Selayang - Risa Damira; Daulat Saragi; Naeklan Simbolon (Randwick International of Education and Linguistics Science Journal, 2023)
This research aims to determine the feasibility, practicality and effectiveness of audiovisual media in the form of animation for class IV students at SD Negeri 067245 Medan Selayang. The research model used is research and development (R&D) using Thiagarajan's 4D design. The research subjects were 54 material and media expert validators, teachers and class IV students, each consisting of 27 students in the experimental class and 27 students in the control class. Based on research findings, validation results by material experts were 87%, media experts 88% and were included in the valid (feasible) category. Furthermore, the practicality results obtained from the teacher questionnaire results were 87.5% in the "Very Practical" category and student responses obtained a percentage of 90% in the "Very Practical" category. It can be concluded that the media developed is practical to use. The pretest score in the experimental class showed an average result of 63 and the posttest score showed an average result of 91, N-Gain 0.8. With the "High" criterion, obtained a value of 0.000 in the t test where Sig <0.05 so it was stated that there was a significant difference Between the learning results in the experimental class and the control class, that audiovisual learning media in the form of animation is very feasible, practical and effective for use in learning and effective in increasing student motivation and learning outcomes.